Genius squad / 2 - Jinks, Catherine (Evil Genius, 2008)
After the Axis Institute is blown up, fifteen-year-old Cadell Piggot is unhappily stuck in foster care with constant police surveillance to protect him from the evil Prosper English until he gets an offer to join a mysterious group called Genius Squad.